Brand Awareness: The Influence of Social Media During the Covid-19 Pandemic - Sitinurbayu Mohd Yusoff; Azeera Azeasharmel Mohd Azreen Azmel (BASKARA : Journal of Business and Entrepreneurship, 2022)
Today, social media is unavoidable, especially as we embrace the 'new normal.' As our use of social media evolves because of the epidemic, it becomes an increasingly valuable communication channel for both brands and consumers. As a result of the current global pandemic and its imposed lockdowns, millions of individuals have resorted to the Internet to socialise. Social media has become an integral part of our everyday lives, not just when we are striving to preserve social distance. Social networking has now become the accepted standard. Marketers have taken notice of this emerging social phenomenon. There has been a change in both customer behaviour and marketing strategies. Consequently, the purpose of this preliminary study is to determine the influence and application of social media as a digital marketing strategy for increasing brand awareness during the Covid-19 pandemic. In Kota Kinabalu, Sabah, 100 respondents were surveyed using an internet questionnaire for a study (Google Form). During Covid-19, social media marketing was effective at increasing brand recognition, according to the findings. Marketers must rethink how they evaluate and target the modern consumer. It is essential to explore and analyse the current situation, since doing so will assist marketing, technology, and communication in the long run.